(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Energy sectors, mainly fossil fuel-fired power plants, contribute to the largest proportion of CO2 production than any other sector. Thus, employing the carbon capture and sequestration (CCS) method in this industry over new or existing facilities has the possibility for the largest reduction in CO2 emissions compared with other industries. The primary focus of this analysis was to assess the effectiveness of two types of solid adsorbents, metal-organic frameworks (MOFs) (Mg-MOF-74, Zn-MOF), and metal oxide (CuO) for the CO2 adsorption process. Scanning Electron Microscope (SEM), Fourier Transform Infra-Red (FTIR), Thermal Gravimetric Analyzer (TGA), Energy Dispersive X-ray (EDX), Brunner Emmet Teller (BET), and X-ray Diffraction (XRD) were applied to characterize the developed adsorbents. From the characterization findings, the analyses affirm the development of Mg-MOF-74, Zn-MOF, and CuO. The effectiveness of the prepared adsorbents was investigated as a function of the test variables: impact of pressure and adsorbent amount. The optimum conditions obtained for the CO2 uptake process for both types of adsorbents were 0.2 g of material amount and 3-4 bar pressure at room condition. Under the optimal parameters, Mg-MOF-74 showed the greatest CO2 adsorption uptake compared to other adsorbents within 150 min of adsorption time. The experimental results offer a deeper understanding of CO2 adsorption in the capturing point of a CCS process. The formulation of novel solid adsorbent materials for CO2 adsorption is also considered the Holy Grail by researchers.